2006
DOI: 10.1248/cpb.54.9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Ruta graveolens L. Extract on Guinea Pig Liver Aldehyde Oxidase

Abstract: Ruta graveolens L. is a flavonoid-containing medicinal plant with various biological properties. In the present study, the effects of R. graveolens extract on aldehyde oxidase, a molybdenum hydroxylase, are investigated. Aldehyde oxidase was partially purified from liver homogenates of mature male guinea pigs by heat treatment and ammonium sulphate precipitation. The total extract was obtained by macerating the aerial parts of R. graveolens in MeOH 70% and the effect of this extract on the enzyme activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Es así, que la administración de Ruta graveolens a dosis bajas (0.5 g/kg) mostró actividad hipoglucemiante, sin embargo cuando se incremento la dosis este efecto disminuyo significativamente. Este fenómeno podría deberse por un lado, a la presencia de diferentes tipos de flavonoides presente en Ruta graveolens como son la rutina y la quercetina (Saieed et al, 2006) en comparación con Cnidoscolus chayamansa y por otro, a la posibilidad de que al aumentar la dosis se este activando otro mecanismo por el cual los niveles de glucosa se incrementen. Por lo tanto, el efecto ejercido por Ruta graveolens al menos es inducido parcialmente a dosis bajas.…”
Section: Discussionunclassified
“…Es así, que la administración de Ruta graveolens a dosis bajas (0.5 g/kg) mostró actividad hipoglucemiante, sin embargo cuando se incremento la dosis este efecto disminuyo significativamente. Este fenómeno podría deberse por un lado, a la presencia de diferentes tipos de flavonoides presente en Ruta graveolens como son la rutina y la quercetina (Saieed et al, 2006) en comparación con Cnidoscolus chayamansa y por otro, a la posibilidad de que al aumentar la dosis se este activando otro mecanismo por el cual los niveles de glucosa se incrementen. Por lo tanto, el efecto ejercido por Ruta graveolens al menos es inducido parcialmente a dosis bajas.…”
Section: Discussionunclassified
“…Ruta graveolens plants and cell cultures accumulate linear furanocoumarins (psoralens) and acridone or furoquinoline alkaloids (Wolters and Eilert 1981;Zobel and Brown 1989;Stashenko et al 2000;Poutaraud et al 2000;Milesi et al 2001;Oliva et al 2003;Hale et al 2004;Kuzovkina et al 2004;Michael 2007) as the predominant secondary metabolites besides aliphatic 2-ketones (De Feo et al 2002) and flavonoids (Wolters and Eilert 1981;Saieed et al 2006;Harborne and Baxter 1999). Acridone alkaloids were detected in all organs particularly in endodermal and vascular tissues (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In the Siparuna guianensis ('negramina') were found flavonoids (Leitão et al, 2005), essential oils (Fischer et al, 2005) and alkaloids (Simas et al, 2001). Ruta graveolens ('arruda') contains alkaloids (Kuzovkina et al, 2004;Michael, 2005), flavonoids (Saieed et al, 2006), coumarins (Kostova et al, 1999), furanocoumarins (Ekiert and Czygan, 2005), triacylglycerines (Asilbekova, 2001) and glycosides (Chen et al, 2001). For Dorstenia asaroides ('caiá-piá') the phytochemical study showed the presence of furanocoumarins (Cardoso et al, 1999).…”
Section: Catalepsy Testmentioning
confidence: 99%